Models of Digital Book Trailers and Applications of Digital Storytelling Approach for Educational Purposes - Maria Dimova; Stanislava Slavova-Petkova; Detelin Luchev (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2018)
The paper presents models for digital book trailers and possibility for their uses for educational purposes. Models and stiles for creation of digital book trailers are discussed. Bulgarian digital book trailers are included as examples of the models. Digital storytelling is presented as a pedagogically valuable approach.